Respuesta :

Answer:

[tex]y = (x - 7)^{2} + 7[/tex].

Step-by-step explanation:

Let [tex]a[/tex], [tex]h[/tex], and [tex]k[/tex] be constants, and let [tex]a \ne 0[/tex]. The equation [tex]y = a\, (x - h)^{2} + k[/tex] represents a parabola in a plane with vertex at [tex](h,\, k)[/tex].

For example, for [tex]y = -(x + 7)^{2} + 7 = -(x - (-7))^{2} + 7[/tex], [tex]a = (-1)[/tex], [tex]h = (-7)[/tex], and [tex]k = 7[/tex].

A parabola is entirely above the [tex]x[/tex]-axis only if this parabola opens upwards, with the vertex [tex](h,\, k)[/tex] above the [tex]x\![/tex]-axis.

The parabola opens upwards if and only if the leading coefficient is positive: [tex]a > 0[/tex].

For the vertex [tex](h,\, k)[/tex] to be above the [tex]x[/tex]-axis, the [tex]y[/tex]-coordinate of that point, [tex]k[/tex], must be strictly positive. Thus, [tex]k > 0[/tex].

Among the choices:

  • [tex]y = -(x + 7)^{2} + 7[/tex] does not meet the requirements. Since [tex]a = (-1)[/tex], this parabola would open downwards, not upwards as required.
  • [tex]y = (x - 7)^{2} - 7[/tex] does not meet the requirements. Since [tex]k = (-7)[/tex] and is negative, the vertex of this parabola would be below the [tex]x[/tex]-axis.
  • [tex]y = (x - 7)^{2} + 7[/tex] meet both requirements: [tex]a = 1[/tex] and [tex]k = 7[/tex].
  • [tex]y = (x - 7)^{2}[/tex] (for which [tex]k = 0[/tex]) would touch the [tex]x[/tex]-axis at its vertex.

Answer:

its c

Step-by-step explanation: